Current State the Problem of Antibiotic Resistance of Pathogens - T. A. Efimenko; L. P. Terekhova; O. V. Efremenkova (Антибиотики и Химиотерапия, 2020)
The problem of antibiotic resistance of pathogenic bacteria is considered, data on antibiotics introduced into medical practice since 2000 in the world, information about existing programs and strategies to prevention antibiotic resistance are given.